Strategy for The Development of Processed Food Products Based on Local Wisdom in South Halmahera - Abdul Hadi Sirat; Hartaty Hadady; Ikbal M. Aris Ali (AIBPM Publisher, 2020)
The purpose of this research is to design a strategy for developing superior processed food products to encourage economic growth in South Halmahera Regency. Using a SWOT analysis, the research findings are increasing community participation in increasing their production capacity through collaboration with other institutions (SO strategy); 2) utilizing technology to enhance people's creativity create more competitive products (WO Strategy establishing a soft approach to the community to support government programs (ST Strategy); increas coordination with the village government to ascertain the program is successfully proven (WT strategy). The results of this study indicate that the government program in developing processed products has not been fully implemented by the community. Therefore, further research should develop by adding key informants.